STEM-11. DIRECTED NEURONAL DIFFERENTIATION AS A THERAPEUTIC STRATEGY FOR MALIGNANT GLIOMAS. (5th November 2018) - Audia, Alessandra; Ravikumar, Visweshwaran; Deng, Zhong; Murali, Vineeth; Balasubramaniyan, Veerakumar; de Groot, John; Rao, Arvind; Bhat, Krishna
Abstract: IDH-mutant (IDH-MUT) glioma patients show highly improved prognosis compared to those with wild-type IDH. However, IDH mutations are rare in the more aggressive grade IV glioblastomas and introducing IDH mutations in mouse neural cells does not induce gliomagenesis. This is a paradox, given that IDH mutation is considered an early oncogenic event and the mutated IDH produces the oncometabolite 2-hydroxyglutarate. Here we identify a previously unknown mechanism that explains this paradox. We found that IDH-MUT patient tumors expressing a molecular signature enriched in genes associated with neuronal differentiation survive the longest (~11 years) and these same tumors have significantly lower expression of the Mesenchymal master regulator TAZ, which is epigenetically silenced. Concordantly, IDH-MUT/TAZ-low glioma stem-like cells (GSCs) show remarkable neuronal differentiation induced by retinoic acid, whereas IDH-WT/TAZ-high GSCs are resistant to this process implying that IDH status and TAZ levels dictate propensity to neurogenesis. TAZ overexpression in IDH-MUT GSCs caused inhibition of retinoic acid neuronal differentiation and conversely CRISPR/Cas9-mediated knockout of TAZ in IDH-WT GSCs promotes this process as judged by alteration in genes regulating neurogenesis as well as cellular morphology resembling neurons (dendritic branching etc.). Preliminary data on the mechanism of TAZ inhibition, indicate that TAZ might directly act as inhibitor of gene expression via formation of a complex with HDAC-1 and -2. Verteporfin, a FDA approved inhibitor of TAZ caused reduction of tumor volume and improved survival in xenograft bearing mice. We are currently evaluating brain penetrating HDAC inhibitors for their ability to induce neuronal differentiation and tumor inhibition in intracranial models of GBM. Taken together, our studies uncover a role for TAZ as a barrier for terminal neuronal differentiation and that differentiation therapy TAZ or HDAC inhibitors is possible for IDH-WT gliomas if combined with retinoids.